Synthesis of novel N-cyclopentenyl-lactams using the aube reaction - Shinde, Madhuri V.; Ople, Rohini S.; Sangtani, Ekta; Gonnade, Rajesh G.; Reddy, D. Srinivasa (Beilstein Journal of Organic Chemistry, 2015)
A novel and convenient method utilizing the Aube reaction to access a new class of compounds that are similar to carbocyclic nucleosides is reported. The azido alcohol derived from Vince lactam undergoes the Aube reaction with various cyclic ketones to give cyclopentenyl-substituted lactams. Upon dihydroxylation, this affords the N-cyclopentenyl-lactam compounds in racemic form. Given the numerous uses of nucleosides and related compounds, we were interested in the synthesis of carbocylic nucleoside mimics. The attempts and results are described herein.
Keywords: Aube reaction; Biological activity; carbocyclic nucleosides; cyclopentenylated lactams; cyclopentylated lactams

Total synthesis of (-)-nardoaristolone B - Ople, Rohini S.; Handore, Kishor L.; Kamat, Nidhi S.; Reddy, D. Srinivasa (European Journal of Organic Chemistry, 2016)
A stereoselective total synthesis of (-)-Nardoaristolone B, a nor-aristolane sesquiterpenoid natural product with an unusual 3/5/6 tricyclic ring system is described. The highlights of the present work includes use of (+)-(R)-Pulegone as a chiral-pool starting material, ring-closing metathesis, allylic oxidation and stereoselective cyclopropanation. In addition, a new analogue of Nardoaristolone B (minor product from the final step) was isolated in pure form and fully characterized with the help of single-crystal X-ray analysis.
Keywords: Chiral pool; cyclopropanation; Nardoaristolone B; Natural products; Total synthesis